Physiological characterization of Carica papaya L. variety UN Cotové - Loaiza-Ruiz, Ruby Alejandra; Cartagena, José Régulo; Barrera-Sánchez , Carlos Felipe; Córdoba-Gaona , Oscar de Jesús (Revista de Ciencias Agrícolas, 2023)
The application of plant physiological principles in genetic improvement allows to approach with greater ease, the solution of the limitations of the agricultural production in an integral and articulated way. For this reason, physiological indicators were used as criteria for the selection of UN Cotové papaya variety plants, which serve as parents for a species breeding program. Eighteen individuals were selected for monthly gas exchange measurements, chlorophyll fluorescence, and leaf area index. The data analysis was done with multivariate non-hierarchical clustering and factorial analysis. Two clusters were generated that did not group morphotypes regarding the gas exchange, quantum yield of Photosystem II (PSII), and leaf area index (LAI). ANOVA established significant differences between plants for most variables. The means were compared with the Tukey test (P < 0.05). Six plants presented better yield, positioning them as a promising material to obtain a papaya variety with outstanding characteristics under tropical dry forest (TDF) conditions.